Late Holocene geochemical signature of inter reef mixed sediments on the northeastern Brazilian outer shelf - Nascimento Silva, Luzia Liniane do; Gomes, Moab Praxedes; Eichler, Patricia Pinheiro Beck; Vital, Helenice (Quaternary and Environmental Geosciences, 2024)
The northeastern outer shelf in Brazil is a complex ecotone that holds significant information on Holocene sedimentary processes and evolution. X-ray diffraction (XRD), X-ray fluorescence (XRF), and scanning electron microscopy/energy dispersive spectrometry (SEM/EDS) were employed to investigate bioclastic sedimentary facies and patches of relict siliciclastic sands. Radiocarbon dating (AMS) indicates that the carbonate sediments and corals formed in the past millennium. The sediment samples were divided into two groups using a multivariate analysis of XRD and XRF. The first group consists of siliciclastic materials, characterized by Si, Al, Fe, K, Zr, and Ti, and has low levels of carbonate and organic matter. The second, bioclastic and mixed facies, has a high carbonate content and exhibits elevated concentrations of Ca, Sr, and Mg, indicating authigenic processes. The EDS data revealed that the shells predominantly consisted of Cl, Cu, Al, Fe, and Ca. The terrigenous sites are detached from the coastal sources and are mainly located within the reef areas of the outer shelf. The erosion processes in these areas were inefficient to eliminate the siliciclastic sediments. This deposit trapped in inter reef sediments holds the key to understanding the timing and interactions between past coastal processes, shelf valley incision, and reef evolution during the Late Holocene transgression.